Membangun Brand Awareness melalui Digital Marketing pada Kelompok UMKM RUFATA: Creating Brand Awareness through Digital Marketing at RUFATA MSME Group - Risqiani, Renny; Murtiningsih, Retno Sari; Riorini, Sri Vandayuli; Walidaeni, Ihsanul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The development of internet technology is currently widely utilized by business people, such as in marketing communications which were originally carried out conventionally, turning into digital marketing. Through digital marketing, business people such as MSMEs can promote their brands so that they are easily recognized by consumers. Building brand awareness is one of the keys to supporting the marketing of a product. The problem faced by the RUFATA MSME Group is the lack of knowledge about product marketing and the lack of digital literacy that needs to be found a way out. People in general are familiar with and use social media, but have not utilized it in marketing their products. For this reason, it is necessary to carry out Community Service (PkM) activities that can provide insight to MSME players regarding an understanding of product marketing, namely how to build brand awareness through digital marketing. The activity was carried out by providing counseling to participants regarding the role of digital marketing in building brand awareness. The results obtained by the participants can understand the material presented and will use it to develop their business.